Evaluating Pericoronary Adipose Tissue Attenuation to Predict Cardiovascular Events - Takahiro Nishihara, MD, PhD; Toru Miyoshi, MD, PhD; Kentaro Ejiri, MD, PhD; Kazuhiro Osawa, MD, PhD; Soichiro Fuke, MD, PhD; Kousuke Seiyama, MD; Masayuki Doi, MD, PhD; Mitsutaka Nakashima, MD, PhD; Takashi Miki, MD, PhD; Shinsuke Yuasa, MD, PhD (JACC: Asia)
Background: Pericoronary adipose tissue attenuation (PCATA) is a novel imaging biomarker of pericoronary inflammation associated with coronary artery disease. Several studies have reported the usefulness of PCATA among people of European ethnicity; however, data are lacking concerning those of Asian ethnicity. Objectives: This multicenter study aimed to evaluate the effect of PCATA on prognosis in East Asian patients. Methods: Between August 2011 and December 2016, 2,172 patients underwent clinically indicated coronary computed tomography angiography (CTA) at 4 hospitals in Japan. Among them, 1,270 patients were analyzed. PCATA was evaluated using coronary CTA to measure pericoronary adipose tissue density surrounding the 3 major coronary arteries. The outcomes were composite cardiovascular events, including cardiovascular death and acute coronary syndrome; 33 cardiovascular events observed during a median follow-up of 6.0 years (Q1-Q3: 3.6-8.2 years). Results: Right coronary artery (RCA)-PCATA was significantly higher in patients with cardiovascular events than in those without (−63.7 ± 8.9 HU vs −67.4 ± 9.1 HU, respectively; P = 0.021). High RCA-PCATA was significantly associated with cardiovascular events in a model that included the Hisayama risk score and adverse coronary CTA findings (HR: 1.55; 95% CI: 1.07-2.24; P = 0.019). Conclusions: High RCA-PCATA showed significant association with future cardiovascular events after adjusting conventional risk factors and adverse coronary CTA findings in East Asian patients who underwent clinically indicated coronary CTA.